2005
DOI: 10.1303/jjaez.2005.262
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Feeding on the Attractiveness of Riptortus clavatus (Thunberg) (Heteroptera: Alydidae) Males to Conspecific Individuals.

Abstract: Abstract:We investigated the effect of the feeding conditions of Riptortus clavatus (Thunberg) males on their attractiveness to conspecific individuals as part of a preliminary study to clarify the adaptive significance of the attraction. Males allowed to take food were found to attract a significantly larger number of conspecific adults than those not allowed. Moreover, males allowed to take food were found to have a significantly more developed fat bodies than those not allowed. The close relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 10 publications
(4 reference statements)
1
15
0
1
Order By: Relevance
“…In R. pedestris, non-diapausing males provided with food were found to have more developed fat bodies and to attract a larger number of conspecific adults than those males without food (Morishima et al, 2005). Mizutani et al (2007) showed that there was individual variation in R. pedestris males in their attractiveness to the same species, and in the amount of pheromone produced.…”
Section: Effects Of Temperaturementioning
confidence: 99%
“…In R. pedestris, non-diapausing males provided with food were found to have more developed fat bodies and to attract a larger number of conspecific adults than those males without food (Morishima et al, 2005). Mizutani et al (2007) showed that there was individual variation in R. pedestris males in their attractiveness to the same species, and in the amount of pheromone produced.…”
Section: Effects Of Temperaturementioning
confidence: 99%
“…In R. pedestris, feeding and attraction to conspecific individuals are closely related (Morishima et al, 2005), suggesting that the pheromone system of R. pedestris plays a key role in food exploitation (Yasuda et al, 2007b). A similar strategy was proposed in the pheromone system of the brownwinged green bug, Plautia crossota stali (P. stali) (Heteroptera: Pentatomidae) (Shiga and Moriya, 1989) and the predatory spined soldier bug, Podisus maculiventris (Heteroptera: Pentatomidae) (Aldrich et al, 1984;Sant'Ana et al, 1997;Shetty and Hough-Goldstein, 1998).…”
Section: Introductionmentioning
confidence: 83%
“…In R. pedestris, males provided with food only released three pheromone components (14:iBu, E2-6:E2Hx and E2-6:Z3Hx) (Leal et al, 1995) and such males attracted adults and nymphs (Morishima et al, 2005). Morishima et al (2005) suggested that pheromone release in males was affected by their fat-body development. These results suggest that the production of 14:iBu is closely related to fat-body development.…”
Section: Discussionmentioning
confidence: 99%